2000
DOI: 10.1002/1097-4628(20010228)79:9<1693::aid-app190>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The effect of talc on the crystallization of isotactic polypropylene

Abstract: Isotactic polypropylene (iPP) has been crystallized in the presence of talc under the quiescent state and shear flow of injection molding. The resulting morphology has been investigated by means of polarizing microscopy, transmission electron microscopy, and wide angle X‐ray diffraction. In the quiescent state, the iPP lamellae grew from the surface of talc and the transcrystalline region was formed at the interface between iPP melt and the talc. The nucleation of iPP was very frequent on the cleavage plane of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 28 publications
3
27
0
2
Order By: Relevance
“…[32][33][34] In this study, we have confirmed the nucleation and crystallization efficiency of talc containing PBT. [32][33][34] In this study, we have confirmed the nucleation and crystallization efficiency of talc containing PBT.…”
Section: Introductionsupporting
confidence: 59%
“…[32][33][34] In this study, we have confirmed the nucleation and crystallization efficiency of talc containing PBT. [32][33][34] In this study, we have confirmed the nucleation and crystallization efficiency of talc containing PBT.…”
Section: Introductionsupporting
confidence: 59%
“…Widely used in many industrial areas such as paper, paints, ceramics, cosmetics and pharmaceutics, talc is very frequently added to polypropylene (PP) to improve its mechanical properties, its thermal resistance and its dimensional stability and all these at a low cost. It is well known that talc acts as a nucleating filler (Naiki et al, 2001;Ferrage et al, 2003) thereby modifying the crystallinity and consequently the mechanical properties of PP (Premalal et al, 2002;Leong et al, 2004;Lapcik et al, 2008). Usually, the fine spherulitic microstructure achieved in PP after adding talc greatly enhances ductility and strength.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of polymer matrices such as iPP having poor if any interaction with the nanofillers, surface treatment techniques of the nanoparticles were required as well as specific preparation methods involving the use of compatibilizing agents. Among mineral fillers, talc proved to have a good potential of development for iPP-based composites, noticeably in the automotive industry [13][14][15][16][17]. It appeared very soon that talc displayed a strong nucleating effect for iPP [14,[19][20][21][22][23] due to specific physico-chemical interactions between the filler and the polymer matrix that promote epitaxial crystallization [14,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%